THE APPLICATION OF LESSON STUDY AND STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Muh Saeful Effendi (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Lesson Study is a school system to improve instruction by conducting collaboration among teachers to plan, observe and reflect the lesson. This system provides one way in which teachers can systematically improve instruction and decrease teacher isolation. Lesson study provides a process for teachers to collaborate and design lessons while examining successful teaching strategies to increase student learning. This paper aims at elaborating the experience of SMPN 1 Srandakan Bantul Yogyakarta in implementing Lesson Study focusing on the correlation between students perception on Lesson Study toward the students English learning achievement. The students’ perception on Lesson Study involves the teacher performance, the class activity, media and the environment that are created by the teacher during the lesson. While the students’ English learning achievement are taken from the final exam score of semester I in the 2011/2012 academic year.The finding indicates that the students’ perception on Lesson Study had a positive and strong correlation with the students’ English learning achievement. Recommendation drawn from this study included an emphasis on improving Lesson Study as a way to improve teachers’ performance in conduction lesson which will consequently improve students’ English learning achievement.